Foodborne Microbiological Hazards in Ghana: A Scoping Review - Wisdom K Ahiabor; Fleischer C N Kotey; Patience B Tetteh-Quarcoo; Eric S Donkor (SAGE Publishing, 2024)
Background: Foodborne diseases pose a significant public health threat, particularly in regions with poor sanitation and food handling practices. These diseases, mainly caused by microbiological hazards like bacteria, fungi, and parasites, affect millions globally. Despite the global burden, the true extent of these hazards remains underestimated, especially in low- and middle-income countries like Ghana. This study aimed to map the available literature on foodborne microbiological hazards in Ghana, providing an overview of the evidence and identifying areas where further research is needed. Method: This review followed the Preferred Reporting Items for Systematic Reviews and Meta-analysis Extension for Scoping Reviews. A detailed search was done in PubMed, Scopus, Web of Science, and Google Scholar, and articles were exported to Rayyan for screening. A three-phase screening process was used to identify relevant articles. Data from the included articles were extracted and analysed, with specific information related to food type, specific hazards, sample population, and hazard groups summarised using proportions and tables. Results: This review included 72 studies which were published between 2001 and 2023. Eighty-five percent of these studies (85%) reported on bacterial hazards, while 19%, 11%, and 6% reported on fungi, parasites, and mycotoxins, respectively. The most reported bacterial, fungal, and parasitic hazards were Escherichia coli , Aspergillus spp. and Trichuris trichiura , respectively. Aflatoxins were reported in maize, groundnut, and spices, with prevalence ranging from 61% to 100% and at levels exceeding standards set by Ghana Standards Authority and European Food Safety Authority. Conclusion: This review highlighted the spectrum of microbiological hazards in foods in Ghana. The hazards identified pose significant public health risks, particularly among vulnerable populations. It is crucial that stricter enforcement of food safety laws and improved food handling practices are implemented in the country, particularly in the informal food sector, to protect consumers.